Acute Interstitial Nephritis in the Pediatric Population: A Review of Etiologic Associations, Histologic Findings, and Clinical Outcome. (January 2023) - Biederman, Laura E.; Conces, Miriam; Shenoy, Archana
Background: Acute interstitial nephritis (AIN) is an infrequent cause of acute kidney injury in the pediatric population with a broad range of etiologies. This retrospective review attempts to characterize AIN in the pediatric population, delineate etiologic factors, histologic features, and clinical outcome. Materials and Methods: Institutional pathology reports were queried for a diagnosis of AIN between 1/2010 and 10/2021. Archived slides and reports and clinical records were reviewed. Results: Twenty-four patients were identified whose ages ranged from 5 to 20 years. A 8 cases (37.5%) were characterized as tubulointerstitial nephritis and uveitis (TINU), 4 cases (16.7%) were associated with an autoimmune disease, 4 cases (16.7%) were likely drug induced, and 8 cases (37.5%) had unclear etiology. Discussion: Although all cases of drug induced interstitial nephritis contained eosinophils they were not exclusive to drug induced interstitial nephritis. A prominent plasma cell infiltrate was seen in both cases of Sjögren's associated interstitial nephritis. The vast majority (n = 18, 75%) showed an improved serum creatinine (<1 mg/dL) 1 year post diagnosis/at last follow-up. In this pediatric series of AIN, TINU contributed to a large subset of cases with known etiologies. On follow up, majority of the cases demonstrated recovery of renal function.